ADJOURNMENT OF CONGREGATIONAL PRAYER DURING COVID-19 PANDEMIC ACCORDING TO FIQH PERSPECTIVE - Kashim, Mohd Izhar Ariff Mohd; Mohamad, Mohd Nasran; Safiai, Mohd Hafiz; Mokhtar, Mohd Helmy; Safri, Lenny Suryani; Hasim, Nur Asmadayana (The journal of contemporary issues in business and government, 2021)
The five-time prayer is the essence of religion that must be performed daily. The impetus of prayer to Muslims is to assure that human relationship with God is always close and hinders one from performing sinful and evil acts. This fard (obligatory) prayer will be more meaningful if performed in the congregation because of its abundant rewards instead of individual prayers. Besides, congregational prayer can educate people to become human beings sensitive to the sense of life as servants and absolutely in line with Maqasid Syariah’s requirements. Nevertheless, currently, the whole world is hit by COVID-19 pandemic. Thus, almost all Islamic countries’ governments must administer proactive steps by introducing Movement Control Orders (PKP) to adjourn all religious activities, including mosque and surau activities. This research aimed to analyse the need for congregational prayer in the mosque or at home.Accordingly, it explained the rational arguments of the adjournment of all worship houses’ activities during the pandemic. This study adopted a descriptive qualitative method of literature review and document analysis. The outcomes revealed that although the pandemic of the COVID-19 epidemic affects Islamic practices, its teachings persists through mosques or surausin the form of a call to prayer every prayer time. Each state’s muftis must deliver proactive steps in issuing fatwas to achieve the maslahahof life preservation from the COVID-19 virus. Congregational prayers can continue but performed in their respective homes. It is to ensure that the transmission of the COVID-19 outbreak is controlled and its chain is broken.